Phase transformation behaviours of porous NiTi SMA fabricated as hollow and solid cylinders by SHS - Kaya, M.; Orhan, N.; Tosun, G. (Maney Publishing, 2010)
Porous NiTi shape memory alloys were fabricated as hollow and solid cylinders by self-propagating high temperature synthesis for use as implant material. The green compacted specimens were synthesised with different ignition technical, high voltage electric arcs. The pore morphologies, microstructures and phase transformation behaviours of the synthesised products at different preheating temperatures were studied. It was seen that the B2(NiTi) and B19'(NiTi) phases were predominant phases. It was also seen that porosity decreased with the increase in preheating temperature and the orientation of the combustion channels was affected by the ignition location. Phase transformation temperatures and activation energies were not changed, but the changes at enthalpy and entropy increased with increasing porosity.
Keywords: Porous NiTi SMA; Powder metallurgy; Preheating temperature; Ignition location; Phase transformation